The efficiency of cryptocurrency in portfolio diversification: evidence from the Covid-19 pandemic - Boodhun, Heshina (2022)
The aim of this study is to evaluate the efficiency of integrating cryptocurrencies in a diversified equity portfolio. Two main hypotheses were tested. The first one investigates the co-movements between equity indices values and cryptocurrencies values to evaluate the latter’s diversification benefits. In view that literatures have concluded that economic downturns increase the correlation among assets, the second hypothesis of this paper evaluates portfolio diversification following the different market phases, by closely considering the COVID-19 pandemic.